Conservation Analysis of Dengue Virus T-cell Epitope-Based Vaccine Candidates Using Peptide Block Entropy - Olsen, Lars R.; Zhang, Guang Lan; Keskin, Derin B.; Reinherz, Ellis L.; Brusic, Vladimir (Frontiers in Immunology, 2011)
Broad coverage of the pathogen population is particularly important when designing CD8+ T-cell epitope vaccines against viral pathogens. Traditional approaches to assembling broadly covering sets of peptides are commonly based on assembling highly conserved epitopes. Peptide block entropy analysis is a novel approach to assembling sets of broadly covering antigens. Since T-cell epitopes are recognized as peptides rather than individual residues, this method is based on calculating the information content of blocks of peptides from a multiple sequence alignment of homologous proteins rather than individual residues. The block entropy analysis provides broad coverage by variant inclusion, since high frequency may not be the sole determinant of the immunogenic potential of a predicted MHC class I binder. We applied block entropy analysis method to the proteomes of the four serotypes of dengue virus and found 1,551 blocks of 9-mer peptides, which covered all available sequences with five or fewer unique peptides. In contrast, the benchmark study by Khan et al. (2008), resulted in 165 9-mers being determined as conserved. Many of the blocks are located consecutively in the proteins, so connecting these blocks resulted in 78 conserved regions which can be covered with 457 subunit peptides. Of the 1551 blocks of 9-mer peptides, 110 blocks consisted of peptides all predicted to bind to MHC with similar affinity and the same HLA restriction. In total, we identified a pool of 333 peptides as T-cell epitope candidates. This set could form the basis for a broadly neutralizing dengue virus vaccine. The peptide block entropy analysis approach significantly increases the number of conserved peptide regions in comparison to traditional conservation analysis of individual residues. We determined 457 subunit peptides with the capacity to encompass the diversity of all sequenced DENV strains.